Synthesis of Symmetrical and Unsymmetrical 1,4-Dithiins by Rhodium-Catalyzed Sulfur Addition Reaction to Alkynes - Arisawa, Mieko; Ichikawa, Takuya; Tanii, Saori; Yamaguchi, Masahiko (Synthesis, 2016)
A convenient synthetic method for 1,4-dithiins was developed using sulfur and alkynes. A rhodium complex catalyzes the addition reaction of sulfur with cyclic alkynes giving the corresponding symmetrical 1,4-dithiines under reflux conditions in 2-butanone. Unsymmetrical 1,4-dithiins are synthesized by the reaction of sulfur with dialkyl acetylenedicarboxylates in the presence of cyclic alkynes or vinyl ethers.
Keywords: sulfur; 1,4-dithiins; rhodium; addition reaction; alkynes